Bi-objective airport slot scheduling considering scheduling efficiency and noise abatement. (February 2023) - Feng, Huilin; Hu, Rong; Wang, Deyun; Zhang, Junfeng; Wu, Chuntao
Abstract: This paper aims to explore the contribution of slot allocation to noise abatement at schedule coordinated airports. To this end, we first build a single-airport bi-objective model that incorporates scheduling efficiency and noise reduction. We then find and analyze a solution that maximizes airport noise reduction with the greatest allocation efficiency. The price of noise reduction is proposed to gain the trade-off between efficiency and environmental benefits. Our research shows that slot scheduling can reduce noise at Shanghai Hongqiao International Airport. The maximum noise reduction schedule shows high fluctuation in the temporal distribution of slots. The price of noise reduction is very high under the maximum noise reduction schedule, and the required displacement to reduce one unit of noise increases sharply as the noise reduction value rises. Besides, the airport capacity expansion plays an essential role in reducing the price of noise abatement.